Farmer participatory screening of maize seed varieties for suitability in risk prone, resource-constrained smallholder farming systems of Zimbabwe - Foti, Richard; Mapiye, Cletos; Mutenje, Munyaradzi; Mwale, Marizvikuru; Mlambo, Nyararai (Global Journal of Food and Agribusiness Management, 2018)
The top down approach to hybrid seed production and variety selection in Sub-Saharan African countries has resulted in farmers being reduced to simple adopters of seed varieties mostly not suited to their pedo-climatic conditions and socio-economic circumstances. This has led to rates of take-up of these seed varieties being painstakingly slow, a situation that threatens to thwart efforts directed at the attainment of food security in the region. In this study, farmer participatory research techniques were used to screen maize seed varieties for their suitability in the semi-arid risk prone areas of Zimbabwe. Farmers were found to prefer drought resistant short season varieties and to retain seed from previous harvests for future planting seasons reflecting their tendency towards risk aversion. The study thus buttresses the need to include farmers in research geared at generating and selecting maize seed varieties that are suitable to their local environments.